Vocational high school or vocational college? Comparing the transitions from school to work - Cristina Lopez-Mayan; Catia Nicodemo (Institute for the Study of Labor (IZA), 2012)
Using a specific micro-dataset with information on working histories, we analyse the labour market entry of Spanish youths who have completed vocational education. According to the education system, young people can enter the labour market with vocational high school (upper secondary education) or with vocational college (tertiary education). Both present a period of workplace training, although, as they belong two distinct schooling levels, they have different entry requirements. Those who complete vocational college has spent more years in education and we would expect more success in finding a first job. Surprisingly, results do not confirm this hypothesis. We do not find important differences in the estimates of the determinants of transitions across types of vocational education. Apprenticeship has a very important role on increasing the hazard rate to employment and this result holds after controlling for unobserved heterogeneity and previous labour experience.
urn:nbn:de:101:1-201204239788
Keywords: J13; J24; I20; 330; duration models; vocational education; labour market entry; apprenticeship; Junge Arbeitskräfte; Berufseinstieg; Betriebliche Ausbildung; Hochschule; Bildungsabschluss; Vergleich; Spanien